PAEDIATRIC CHOLESTEATOMA – A CLINICORADIOLOGICAL AND HISTOPATHOLOGICAL STUDY WITH SURGICAL OUTCOMES (Asian Journal of Medical Research and Health Sciences, 2026)
Objective- To study the varying presentations of 10 cases diagnosed with Paediatric Cholesteatoma in a Tertiary Care Hospital Study Design- A prospective study of 10 patients from January 2025 to January 2026 Subject And Methods- Patients who presented to the ENT OPD of our hospital were admitted and examined in detail. Patients were then planned for Canal Wall Up or Canal Wall down mastoidectomy. Histopathological Diagnosis was used to confirm Cholesteatoma and then the patients were studied based on age, sex, presenting chief complaints, examination and radiological findings. Results- In our study done over a period of 1 year, we diagnosed and managed 10 cases of cholesteatoma in paediatric age group (